Bi2O3 Nanoparticles Decorated Carbon Nanotube: An Effective Nanoelectrode for Enhanced Electrocatalytic 4-Nitrophenol Reduction - Dighole, Raviraj P.; Munde, Ajay V.; Mulik, Balaji B.; Sathe, Bhaskar R. (Frontiers in Chemistry, 2020)
4-Nitrophenol (4-NP) present in most of the industrial waste water as an organic pollutant and it is highly toxic in nature & environmental hazardous pollutant. Here we report the Bi2O3@MWCNTs are most prominent electrocatalyst for 4-nitrophenol electroreduction in acidic condition. The electrocatalyst synthesized by simple chemical reduction method by using ethylene glycol as capping agent. Bi2O3@MWCNTs characterized by Furier-Transform Infrared (FT-IR) spectroscopy, Transmission electron microscopy (TEM), X-ray diffraction (XRD), and Raman spectroscopy. Bi2O3@MWCNTs are in cubic structure which is confirmed by XRD and TEM image reveals Bi2O3 NPs are having ~2 nm which are grown on MWCNTs, these nanoparticles are active towards 4-paranitrophenol electroreduction. The electrochemical test study by cyclic voltammetry shows that electrocatalysts can sense 4-NP at very lower potential at -0.37 vs. SCE & further chronoaprometry and Impedance spectroscopy studies were carried out.